Efeitos do óleo essencial de Cymbopogon citratus Stapf (Capim-limão) sobre o processo de carcinogênese química em fêmeas BALB/C - Bidinotto, Lucas Tadeu [UNESP] (2008)
Lemongrass (Cymbopogon citratus STAPF) has been described as a potential chemopreventive agent. Thus, the present study objectives were evaluate the protective effects of oral treatment with lemongrass essential oil (LGEO) on carcinogenesis initiation phase with N-methyl-N-nitrosurea (MNU) and post-initiation carcinogenesis phase in multipleorgans model, through 7,12-dimethylbenz(a)antracene (DMBA), 1,2-dimethylhidrazine (DMH), and N-buthyl-N-(4-hidroxibuthyl)nitrosamine (BBN) administrations in Balb/C female mice. The animals were distributed into 2 experimental protocols. Experiment 1: the animals were allocated into 3 experimental groups: G1A group (negative control), G2A group (treated with LGEO 500 mg/kg b.wt., i.g., during 5 weeks and, at the end of the 3rd and 5th weeks, received one 30 mg/kg MNU i.p. application) and G3A group (treated with the LGEO vehicle, and MNU at the end of the 3rd and 5th weeks). After 4 hours of each MNU application, blood samples were collected to perform the comet assay, and, at the end of the 5th week, all animals were euthanatized and the urinary bladder, mammary glands and colon were collected for histological analysis, apoptosis and cellular proliferation counting. Experiment 2: the animals were allocated into 3 experimental groups: G1B group (positive control, DDB-treated animals), initiated with DMBA (5x1 mg i.g. applications), DMH (4x30 mg/kg s.c. applications) and BBN (8x7.5 mg/kg i.g. applications) and treated with the LGEO vehicle, and G2B and G3B groups, similarly DDB-treated, and treated with 125 mg/kg or 500 mg/kg LGEO respectively (5x/week during 6 weeks). At the end of the experimental period, all animals were euthanatized and urinary bladder, mammary glands and colon were collected for preneoplastic and neoplastic lesions analysis. The LGEO treatment reduced DNA damage in peripheral blood leukocytes as well as mammary gland cellular proliferation index.